ICT and its implication on fishermen income in Malaysia - Bolong, Jusang; Omar, Siti Zobidah; Mohamed Shaffril, Hayrol Azril; Alby, Jeffrey Lawrence D'Silva; Abu Hassan, Musa (Medwell Journals, 2013)

(untitled)
As been profited by other industries, the evolution on ICTs has raised its impacts on the fisheries industries. Realizing the impacts, there is abundance of international studies that try to seek the association between ICTs usage and fishermen income. Nonetheless, reverse situation is found in Malaysia where there are still few local studies that place their interest on such association and the main attempt of this study is to investigate the relationship and the contribution of ICT usage towards fishermen income in Malaysia. This is quantitative study where questionnaire was used to gather the required data. A total of 400 registered fishermen from four fisheries districts in Malaysia have been randomly selected as the respondents. Based on the analysis employed, it can be seen that usage of sonar, echo sounder and radar are related to the fishermen income. In addition, further analysis has confirmed that these three tools are contributing towards fishermen income. To encourage ICTs usage among fishermen, it is recommended that the fishermen should be provided with ICT seminars and courses, supports such as financial, accessibility and services. Apart from this, selected behavioral factors should be taken into consideration while implementing strategies with regard to fishermen ICT usage.